L'Islam saharien précolonial: portrait d'un champ de recherche - Warscheid, Ismail (Studia Islamica, 2018)
From the 15th century onwards, a network of Muslim scholarly communities developed in the western and central parts of the Sahara, covering present-day southern Algeria, Mali, Mauritania, Morocco, and Niger. The massive diffusion of Islamic literate culture led to the constitution of a rich tradition of scholarship that materialized in various types of texts: doctrinal treatises, biographical dictionaries, chronicles, commentaries, poetry, and, most important, comprehensive fatwa collections. In the last decades, increasing academic attention has been given to this astonishing cultural heritage of the people of the great desert. This article intends to give a short survey of works and research orientations, focusing on projects of identification and edition of Arabic manuscripts and on the mobilization of Muslim scholarly writing as a source for social and cultural history.